Een heel eigen manier van kijken - Blom, J.C.H. (BMGN - Low Countries Historical Review, 2010)
A Highly Particular Way of Looking In her discussion of the series of television documentaries De Oorlog [The War] in bmgn/lchr 125:1 (2010) 73-99, Barbara Henkes gives an incorrect impression of the intentions of the programme makers. My response will in the first place consist of an exposition of these intentions: principally, to give the best possible presentation of current insights on the basis of recent academic research to a very wide audience. I will then discuss a number of more specific issues in greater detail. In particular, I make the strongest possible objection to the accusation that the makers have pushed morally reprehensible viewpoints onto the audience. Henkes presents no evidence whatsoever to support these accusations, and fails to explain what was actually, factually incorrect in the series. This makes her article nothing more than an (attempt at) moral disqualification. This article is part of the forum ’De Oorlog’.